On nomenclature and synonymy of Trichius rosaceus, T. gallicus, and T. zonatus (Coleoptera: Scarabaeidae: Cetoniinae: Trichiini) - Krell, Frank-Thorsten (Zootaxa, 2012)
The name Scarabaeus rosaceus Voet, 1766–1778, currently in use as one of two names for a west Palaearctic Trichius species, is unavailable because Voet’s work is not consistently binominal. The valid name for the species is Trichius gallicus Dejean, 1821 with the Sardinian and North African populations forming the subspecies T. g. zonatus Germar, 1831. The lectotype of Trichius zonatus Germar is designated.